Varicella zoster virus transmission in youth during incarceration. Issue 2 (13th June 2016) - Moreau, Danusia; Besney, Jonathan; Jacobs, Angela; Woods, Dan; Joffe, Mark; Ahmed, Rabia
Abstract : Purpose: – Facility-based Varicella zoster virus (VZV) transmission is reported in a Canadian youth offender correctional centre (YOCC). Transmission occurred from an immunocompetent youth offender (YO) with localized Herpes zoster to another immunocompetent single dose vaccinated YO, resulting in Varicella zoster (VZ) breakthrough disease. The purpose of this paper is to identify infection prevention and control (IPAC) measures utilized in this setting. Design/methodology/approach: – A retrospective chart and immunization record review was conducted for two VZV cases and 27 exposed YO contacts in order to obtain demographic, clinical and immunization data. Descriptive data analysis was performed. Findings: – All VZV cases and exposed contacts were male with an average age of 14.2 and 15.6 years for cases and contacts, respectively. Both cases shared the same living unit in the YOCC. There were 28 identified YO contacts, of whom 70 percent were single dose vaccinated with univalent vaccine, followed by 22 percent with a previous history of Varicella disease. All cases and contacts were born in Canada. No foreign-born populations were involved with this event. Infection control measures included additional precaution management, enhanced surveillance and environmental cleaning. As such, no hospitalizations or post-exposure immunizations were required. Originality/value: – This report highlights the role that VZ breakthrough disease could play in fueling an outbreak in a high-risk environment without rapid recognition and implementation of preventative measures. It also underscores the importance of IPAC presence and public health immunization programs within correctional centers to avoid infectious disease threats.